2016
DOI: 10.1093/cid/ciw552
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-ResistantStaphylococcus aureusCC398 in Humans and Pigs in Norway: A “One Health” Perspective on Introduction and Transmission

Abstract: This study provides strong, novel evidence that humans may introduce methicillin-resistant Staphylococcus aureus CC398 into closed pig populations; it also demonstrates that stringent control and eradication measures were effective and prevented dissemination from pig farms to the general human population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 22 publications
5
99
0
5
Order By: Relevance
“…For comparative purposes, we included in the WGS-based phylogenetic analysis 16 porcine MRSA CC398 isolates from a previous Danish study (Grøntvedt et al, 2016) and 11 human MRSA CC398 isolates from the national MRSA database. The porcine isolates were selected to represent the three major phylogenetic groups in pigs in Denmark (Larsen, unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…For comparative purposes, we included in the WGS-based phylogenetic analysis 16 porcine MRSA CC398 isolates from a previous Danish study (Grøntvedt et al, 2016) and 11 human MRSA CC398 isolates from the national MRSA database. The porcine isolates were selected to represent the three major phylogenetic groups in pigs in Denmark (Larsen, unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…In the latest survey from 2016, LA-MRSA was found in only one of 872 participating pig farms [12]. The reasons for this success can be explained by restricted import of live pigs and a control strategy which includes recommendations for targeted screening of personnel before working in pig herds, active surveillance of the pig population, and a ‘search and destroy’ policy on pig farms [13]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, there may be differences between the clonal structure of the Danish and Norwegian LA-MRSA populations and their tolerance to cefoxitin and aztreonam at the concentrations used in the 2-S method. Although we did not determine antimicrobial susceptibility or minimum inhibitory concentrations in our study, we do not believe this to be the case, as the vast majority of contemporary LA-MRSA isolates circulating in the Danish and Norwegian pig populations belong to the same clonal complex, CC398 [13,17]. Whole-genome sequencing analysis even showed that LA-MRSA CC398 isolates from the two countries are very closely related [13].…”
Section: Discussionmentioning
confidence: 99%
“…A new MRSA variant, CC398, which was first noted in Finland in 2007, has recently been found in animals, especially intensively reared production livestock such as pigs, cattle and poultry, and can be transmitted to humans (Salmenlinna et al, 2010). Transmission is mainly via occupational exposure, resulting in mild to serious infections and even death (Anderson et al, 2003;Salmenlinna et al, 2010;Smith & Wardyn, 2015;Grøntvedt et al, 2016).…”
Section: Antimicrobial Resistance In Animal Productionmentioning
confidence: 99%